Основні заходи по підвищенню фінансової стійкості підприємств України - Брік, Світлана Володимирівна; Рудковська, Євгенія Михайлівна (НТУ "ХПІ", 2015)
Розглянуто основні характеристики фінансово стійких підприємств, визначено проблеми з фінансовою стійкістю підприємств України, представлено порядок визначення фінансової стійкості підприємства та наведено основні заходи по підвищенню фінансової стійкості підприємств в Україні. Також представлено схематично які підприємства вважаються фінансово стійкими та зроблено відповідні висновки. Одна з основних проблем фінансової стійкості підприємства - переважання запозичення над заходами щодо збільшення власного капіталу, придбання матеріальних цінностей в кредит, без урахування реальної можливості їх оплати грошима.

The main characteristics of financially stable companies identified problems with financial stability of Ukraine, presented the procedure for determining the financial sustainability of the company and are the main measures to improve the financial stability of enterprises in Ukraine. Also represented schematically that companies considered financially stable and the correct conclusions. Thus I can say that the definition of the optimal size of own working capital and the structure of liabilities will allow the owner to maneuver resources, and economic activities in order to improve the efficiency of production and financial activities, to find ways of strengthening the solvency and financial stability of enterprise in a market economy, and create conditions for prevention of undesirable financial situations. Financial stability of the enterprise is closely related to his prospective capacity to pay, its analysis allows us to determine the financial possibilities of the enterprise in perspective. Assessment of financial stability of the enterprise aims at objective analysis of the value and structure of assets and liabilities of an enterprise and determine on this basis a measure of its financial stability and independence, and to comply with financial-economic activity of the enterprise the objectives of its authorized activity.
Key measures to improve the financial stability of enterprises Ukraine
Keywords: рівновага фінансова; інвестиції; капітал; виробництво